Validation of a Proposed Dashboard Model for Researchers In Social Research Network Sites - Siti Hawa, Apandi; Ruzaini, Abdullah Arshah (Asian Research Publishing Network (ARPN), 2015)
The Social Research Network Sites (SRNS), online platform used by researchers, have huge amounts of information that would sometimes overwhelm the researchers. However, they need a dashboard as a tool to provide awareness on current information that are related to their fields of research; thus, the proposed dashboard model for the researchers in the SRNS is designed. This paper aims to discuss the validation of the dashboard model for the researchers in the SRNS by conducting an interview session, which is conducted among the researchers that consists of academic staffs and postgraduate students from the universities in Malaysia. After being shown the dashboard model and the accompanying mock-up prototyping representing the dashboard model, the researchers were asked to gauge their satisfaction on the dashboard model and their intention of using the model. The outcome of the interview is that the researchers are satisfied with and intended to use the dashboard model, while suggesting some enhancement of the dashboard components to be included in the dashboard model. The dashboard model can be used by a developer of the SRNS as a guideline to develop a better online platform for the researchers by including the dashboard in the SRNS.